The Task of Maximising the Satisfaction from on Inwestor's Investment Portfolio - Rutkowska, Aleksandra (Studia Oeconomica Posnaniensia, 2013)
The problem of selecting an investment portfolio has been widely discussed in the literature, based on both a stochastic analysis as well as a fuzzy set theory framework. The most commonly used criterion is to maximize profi t while minimizing risk. Empirical studies conducted among investors have shown that they do not always act in accordance with this principle. Individual investors assess the gains and uncertainty in the light of individual expectations, largely based on emotion and intuition. In this paper a new investment portfolio selection model will be proposed based on the measure of satisfaction. A formal description of the fuzzy environment is used based on the rate of return. Th is model assumes that an investor maximizes their level of satisfaction with an investment, understood as the similarity between the reliability of the fuzzy returns and the investor's expectations. Th e model is illustrated with mathematical examples to illustrate the optimization idea and compare it to the mean-variance model.